Biological Mechanisms Induced by Soybean Agglutinin Using an Intestinal Cell Model of Monogastric Animals - Pan, Li; Liu, Yan; Lan, Hainan; Bao, Nan; Zhao, Yuan; Sun, Hui; Qin, Guixin; Farouk, Mohammed Hamdy (Frontiers in Veterinary Science, 2021)
Soybean agglutinin (SBA) has a toxic effect on most animals. The anti-nutritional mechanisms of SBA are not fully understood, in terms of cell survival activity and metabolism of intestinal cells. This study aims to investigate the effects of SBA on the cell cycle, apoptosis, and to verify the mechanism of SBA anti-nutritional characters based on proteomic-based analysis. The IPEC-J2 cell line was cultured with medium containing 0.0, 0.5, or 2.0 mg/mL SBA. With increasing SBA levels, the percentage of the cells at G0/G1 phase, cell apoptosis rates, expressions of Bax and p21, and the activities of Casp-3 and Casp-9 were increased, while cyclin D1 and Bcl-2 expressions were declined (p < 0.05). The proteomic analysis showed that the numbers of differentially expressed proteins, induced by SBA, were mainly enriched in different pathways including DNA replication, base excision repair, nucleus excision repair, mismatch repair, amide and peptide biosynthesis, ubiquitin-mediated proteolysis, as well as structures and functions of mitochondria and ribosome. In conclusion, the anti-nutritional mechanism of SBA is a complex cellular process. Such process including DNA related activities; protein synthesis and metabolism; signal-conducting relation; as well as subcellular structure and function. This study provides comprehensive information to understand the toxic mechanism of SBA in monogastrics.